Predictive capacity for breastfeeding and determination of the best cut-off point for the breastfeeding self-efficacy scale-short form - Josep Vicent Balaguer-Martínez; Rubén García-Pérez; Ana Gallego-Iborra; Elena Sánchez-Almeida; María Dolores Sánchez-Díaz; Edurne Ciriza-Barea (Elsevier, 2022)
Introduction: The most widely used tool for assessing breastfeeding self-efficacy is the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). This study assesses the relationship between the BSES-SF score and the risk of breastfeeding (BF) cessation and determines the cut-off point in the scale score that optimizes detection of this risk in primary health care pediatric consultations. Methods: Secondary data analysis of the LAyDI study. Cohort study carried out through a research network of primary care pediatricians (PAPenRed). A newborn was recruited every month for one year by 210 pediatricians. The cohort was followed for 24 months. Mothers responded to the BSES-SF at the first visit. General pregnancy and delivery data were collected and assessed to determine whether breastfeeding was exclusive or supplemented during the first 6 months. Results: N = 1845. The Area Under the ROC Curve for the exclusive BF was 0.790 (0.765-0.815) the first month and 0.760 (0.734-0.786) the second month. For 4 and 6 months, as well as for any age in mothers who give supplemented BF, the Area Under the Curve was less than 0.75 and its predictive capacity was not considered to be good. For a sensitivity of 80% in detecting mothers at risk of BF cessation with the BSES-SF, the cut-off score was 58. Conclusions: Mothers with a BSES-SF score below 58 points in primary health care, are at risk of early withdrawal of exclusive BF within two months. Resumen: Introducción: El instrumento utilizado habitualmente para valorar la autoeficacia de la lactancia materna es la Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). Este estudio valora la relación entre la puntuación de la BSES-SF y el riesgo de abandono de la lactancia. También se determina el punto de corte en la puntuación de la escala que optimiza la detección de este riesgo desde Atención Primaria. Métodos: Análisis secundario de datos del estudio LAyDI. Estudio de cohorte única realizado a través de la red de investigación de pediatras de Atención Primaria (PAPenRed). Cada pediatra reclutó un recién nacido cada mes durante un año. Se siguió la cohorte 24 meses. Las madres respondieron la BSES-SF en la primera visita. Se recogieron datos generales de embarazo y parto y se valoró la lactancia materna (suplementada o exclusiva) hasta los 6 meses. Resultados: n = 1845. El Área Bajo la Curva ROC para la LM exclusiva fue al primer mes de 0,79 (0,77-0,82) y al segundo mes de 0,760 (0,734-0,786). Para los 4 y 6 meses, así como para cualquier edad en madres que dan LM suplementada, el Área Bajo la curva fue menor de 0,75 y su capacidad predictiva no se consideró adecuada. Para una sensibilidad del 80% en la detección de madres en riesgo de abandono de la lactancia la puntuación de corte fue 58. Conclusiones: Las madres que en Atención Primaria presenten una puntuación en la BSES-SF por debajo de 58 puntos tienen riesgo de abandono de la lactancia materna exclusiva antes de los dos meses.